Answer:
18 in
Step-by-step explanation:
First you would multiply 2·5=10 then for the area of the bottom shape you already have 4 for one side to get the other side you subtract 7-5 and get 2 so 4·2=8 so then add the areas of both shapes and get 18
Simplify by dividing the two by 14
U/9 = 8/12 u = 6
Step 1: Cancel the common factor (4)
u = 2
—- —-
9 3
Step 2: multiply both sides by 9
9u 2 * 9
—- = ——-
9 3
Step 3: simplify
2 *9 = 18
18 ÷ 3 = 6
u = 6
Answer:
D. b + a = c
Step-by-step explanation:
c – a = b
Add a to both sides.
c = b + a
b + a = c
Answer: D. b + a = c
When it doesn’t look like a U anymore and is upside down
Looking at an equation than when x is negative